Compounding pharmacy regulations: experience of the Latvian pharmaceutical market - D. D. Mamedov; D. S. Yurochkin; D. D. Zelikova; S. E. Erdni-Garyaev; Z. M. Golant; I. A. Narkevich (Фармакоэкономика, 2024)
The article aims to examine technological, organizational and regulatory aspects of drug quality and safety assurance system, as well as peculiarities in civil circulation of extemporaneous drugs in Latvian pharmaceutical market to improve approaches for statutory regulation of this special and socially significant type of activity of pharmaceutical organizations. This work continues a series of articles about compounding pharmacy practice in different world healthcare systems.